1994
DOI: 10.1128/jcm.32.3.746-749.1994
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of PCR with direct examination of bone marrow aspiration, myeloculture, and serology for diagnosis of visceral Leishmaniasis in immunocompromised patients

Abstract: A PCR assay amplifying a repeated sequence from the Leishmania infantum genome was compared with direct examination of bone marrow aspirate, myeloculture, and serology for the diagnosis of visceral leishmaniasis in immunocompromised patients. Of 73 patients living in an area endemic for leishmaniasis and where visceral leishmaniasis was suspected by physicians, only 10 had an indisputable diagnosis of visceral leishmaniasis. None of the diagnostic tests performed in the study achieved 100% sensitivity for diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
1
5

Year Published

1996
1996
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(54 citation statements)
references
References 15 publications
3
45
1
5
Order By: Relevance
“…Statistical analysis was applied to the results of molecular examination, as it was considered the most reliable method of detecting the infection . Therefore, statistical analysis was used to assess the influence of different risk factors to the Leishmania spp.…”
Section: Methodsmentioning
confidence: 99%
“…Statistical analysis was applied to the results of molecular examination, as it was considered the most reliable method of detecting the infection . Therefore, statistical analysis was used to assess the influence of different risk factors to the Leishmania spp.…”
Section: Methodsmentioning
confidence: 99%
“…The combination of two or more serologic techniques may significantly increase the sensitivity of antibody detection, and some authorities have recommended this practice in HIV-infected patients with suspected VL. However, in a study in which several diagnostic methods were compared, 20% of co-infected patients gave negative results with all serologic techniques [39]. The functional impairment of cell-mediated immunity due to HIV infection could result in an absent antibody response to Leishmania, as for other infections.…”
Section: Agnos T Ic Pr Ocedur E Smentioning
confidence: 99%
“…1997a). In another study, comparison of PCR on bone marrow aspirates with microscopic examination and culture for diagnosis of VL in immune‐compromised patients showed that PCR exhibited a higher sensitivity (82%) than microscopy (55%) and culture (55%) (Piarroux et al . 1994).…”
Section: Diagnosismentioning
confidence: 99%